Problematika dan Kepuasan Siswa dalam Menghadapi Pembelajaran Jarak Jauh di Sekolah Menengah - M. Dahlan R; Salma Zahratusholihah; Kholil Nawawi (Universitas Indraprasta PGRI Jakarta, 2021)
The Covid-19 pandemic has resulted changes in education, causing various problems in learning. Because of these problems, there are certain responses from students as a picture of their satisfaction with the learning carried out. This response will determine students' attitudes in learning, thus affecting the achievement of learning objectives. Therefore, the purpose of this study is to determine the problems and student satisfaction in distance learning. The research was conducted using qualitative methods with a field research approach. Data were collected using the observation method, questionnaires given to students via google form, and documentation. Then the data were analyzed through reduction activities, data presentation, and conclusions. The results showed that the problem of distance learning that occurred in SMP Negeri 1 Pamijahan obtained a percentage of 58%, so it was classified as quite good, which inferred that the problem that occurred was not quite serious. The student satisfaction in distance learning obtained a percentage of 67%, thus it was classified as quite satisfactory. The aspects that need improvement because they resulted in bad category were aspects of understanding material and interaction, and less satisfied with aspects of material and learning methods.